2007
DOI: 10.3892/ijmm.19.3.369
|View full text |Cite
|
Sign up to set email alerts
|

A W148R mutation in the human FOXD4 gene segregating with dilated cardiomyopathy, obsessive-compulsive disorder, and suicidality

Abstract: Abstract. The forkhead/winged helix box (FOX) gene family comprises at least 43 different genes encoding transcriptional factors with a highly conserved DNA-binding domain. To date, mutations in members of the FOX gene family have been causally linked to a variety of different human diseases. We describe a three-generation Albanian pedigree in which a complex phenotype consisting of dilated cardiomyopathy, obsessive-compulsive disorder, and suicidality is segregated with a missense mutation (W148R) in the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Finally one missense pathogenic variant has been reported but associated with a complex phenotype consisting of familial DCM, obsessive-compulsive disorder, and suicidality (CM073074) [53].…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Finally one missense pathogenic variant has been reported but associated with a complex phenotype consisting of familial DCM, obsessive-compulsive disorder, and suicidality (CM073074) [53].…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Future unc-130 studies may lead to universal molecular insights into primary neurogenesis. In addition, whole-human genome analysis has implied that FOXD4 is a risk factor for suicide and obsessive–compulsive disorder 67 . Such outcomes may be attributable to vulnerability to stress.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 FOXD4 is a transcription factor (TF) that belongs to the forkhead/winged helix-box (FOX) famil. 9 FOX transcription factors participate in several key processes, such as metabolism, cell proliferation, and metastasi. 10,11 It is reported that mutations in FOXD4 transcription are related to multiple phenotypes including dilated cardiomyopathy, obsessive-compulsive disorders, and suicidalit.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 It is reported that mutations in FOXD4 transcription are related to multiple phenotypes including dilated cardiomyopathy, obsessive-compulsive disorders, and suicidalit. 9 Previous studies have revealed that epithelial-mesenchymal transition (EMT) is an important process preceding tumor metastasi. 12,13 EMT is an evolutionarily conserved developmental process characterized by the conversion of polarized immotile epithelial cells to motile mesenchymal cell.…”
Section: Introductionmentioning
confidence: 99%